The taming of the queen - Gregory, Philippa (New York : Touchstone, 2015)
Kateryn Parr, a thirty-year-old widow in a secret affair with a new lover, has no choice when a man old enough to be her father who has buried four wivesKing Henry VIIIcommands her to marry him.
Includes bibliographical references (pages 445-450)
Keywords: Catharine Parr, -- Queen, consort of Henry VIII, King of England, -- 1512-1548 -- Fiction; Henry -- VIII, -- King of England, -- 1491-1547 -- Fiction; Queens -- England -- Fiction; Biographical fiction; Historical fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction